2010
DOI: 10.1163/187498310x517123
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation of insect succession on carrion in Calabria (southern Italy)

Abstract: We present data from the fi rst study of successional patterns of insect fauna in Calabria (southern Italy). Th e aim was to identify and qualitatively assess the major taxa of forensic importance in this region. Studies were conducted in autumn-winter 2006, summer 2007 and winter 2008 in the Botanical Garden, University of Calabria. Over 50 taxa were collected and identifi ed. Th e most abundant fl y species were Lucilia caesar (Linnaeus, 1758), L. sericata (Meigen, 1826), Chrysomya albiceps (Wiedemann, 1819)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Our results suggest that in the reported case the predatory activity of T. nigerrimum could have interfered with body colonization by flies, which usually reach a body few minutes after death [15,[18][19][20][21]. These data are similar to previously reported ones in which a body was found extensively colonized by ants in almost total absence of eggs and larvae, which presumably foraged on them altering the body decay [22].…”
Section: Discussionsupporting
confidence: 86%
“…Our results suggest that in the reported case the predatory activity of T. nigerrimum could have interfered with body colonization by flies, which usually reach a body few minutes after death [15,[18][19][20][21]. These data are similar to previously reported ones in which a body was found extensively colonized by ants in almost total absence of eggs and larvae, which presumably foraged on them altering the body decay [22].…”
Section: Discussionsupporting
confidence: 86%
“…Diverse studies showed that there is a long history of success in using carabids to signal environmental change [4,8,[33][34][35]. Moreover, changes in landscape such as fragmentation [36,37], recreational use [38], urbanization [39,40], forest management [35,41].…”
Section: Discussionmentioning
confidence: 99%
“…In most past forensic studies of ants, the researchers used carcass baits to attract arthropods, and the resulting collected ants were often a single species in large numbers fully occupying the resource (McGlynn & Kirksey, 2000;Cerda et al, 2013). Some of these studies likely significantly under-sampled true ant diversity by only using hand collection to survey ants (Carvalho et al, 2004;Bonacci et al, 2010), promoting the use of a baited trap mixed with pitfall traps to enhance the sampling of necrophilous ants (Hwang, 2011;Castro et al, 2014;Andrade-Silva et al, 2015). In this study, we developed a simple combination bait-pitfall trap that catches a more representative sample of the true necrophilous ant diversity of a region.…”
Section: Discussionmentioning
confidence: 99%
“…This potential of ants has long been overlooked in forensic entomology, where past surveys of insect succession on carcasses or crime studies usually did not provide specieslevel identification for ants (Carvalho et al, 2004;Moura et al, 2005;Bonacci et al, 2010;Bonacci et al, 2011). Until now, only a few forensic entomology studies in Portugal, Brazil and Taiwan recorded ant species (Hwang, 2011;Castro et al, 2014;Andrade-Silva et al, 2015;Paula et al, 2016).…”
mentioning
confidence: 99%